2016
DOI: 10.17795/jjhr-31079
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Separation of X- and Y-Chromosome Bearing Sperms of Fertile Men by Albumin Gradients Using Real Time PCR

Abstract: Background: One of the techniques used in infertility centers for separating the spermatozoa containing Y or X chromosomes is the Ericsson method. It is simple, cheap, and practical without using any toxic material. There are contradictory reports regarding the efficiency of this extremely reliable method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…On the other hand, many researchers including (17,21,22) confirmed the effectiveness of this method, especially in determining the male gender. Meanwhile, other researchers believed that this method was ineffective (17,23). However, Fugger's study suggests that the health of the baby after delivery has been confirmed by this method (24).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, many researchers including (17,21,22) confirmed the effectiveness of this method, especially in determining the male gender. Meanwhile, other researchers believed that this method was ineffective (17,23). However, Fugger's study suggests that the health of the baby after delivery has been confirmed by this method (24).…”
Section: Discussionmentioning
confidence: 99%
“…1 The reasons include; cultural, social and economic preferences, gene linked diseases and family balancing. 2 Even the infertile patients have significant demand for preimplantation sex selection, with a significant portion of this demand coming from patients who do not have any child or have all children of same sex. 3 The publication of article on separation of X-and Y-bearing spermatozoa using albumin gradients 4 gained high popularity.…”
Section: Introductionmentioning
confidence: 99%